Induction and Resuscitation of Viable but Nonculturable Corynebacterium diphtheriae - Hamabata, Takashi; Senoh, Mitsutoshi; Iwaki, Masaaki; Nishiyama, Ayae; Yamamoto, Akihiko; Shibayama, Keigo (Microorganisms (Basel), 2021)
Many pathogenic bacteria, including Escherichia coli and Vibrio cholerae, can become viable but nonculturable (VBNC) following exposure to specific stress conditions. Corynebacterium diphtheriae, a known human pathogen causing diphtheria, has not previously been shown to enter the VBNC state. Here, we report that C. diphtheriae can become VBNC when exposed to low temperatures. Morphological differences in culturable and VBNC C. diphtheriae were examined using scanning electron microscopy. Culturable cells presented with a typical rod-shape, whereas VBNC cells showed a distorted shape with an expanded center. Cells could be transitioned from VBNC to culturable following treatment with catalase. This was further evaluated via RNA sequence-based transcriptomic analysis and reverse-transcription quantitative PCR of culturable, VBNC, and resuscitated VBNC cells following catalase treatment. As expected, many genes showed different behavior by resuscitation. The expression of both the diphtheria toxin and the repressor of diphtheria toxin genes remained largely unchanged under all four conditions (culturable, VBNC, VBNC after the addition of catalase, and resuscitated cells). This is the first study to demonstrate that C. diphtheriae can enter a VBNC state and that it can be rescued from this state via the addition of catalase. This study helps to expand our general understanding of VBNC, the pathogenicity of VBNC C. diphtheriae, and its environmental survival strategy.